A Finite Element Mesh Aggregating Approach to Multiple-Source Reconstruction in Bioluminescence Tomography - Jingjing Yu; Fang Liu; L. C. Jiao; Shuyuan Yang; Xiaowei He (International Journal of Biomedical Imaging)
A finite element mesh aggregating approach is presented to reconstruct images of multiple internal bioluminescence sources. Rather than assuming independence between mesh nodes, the proposed reconstruction strategy exploits spatial structure of nodes and aggregation feature of density distribution on the finite element mesh to adaptively determine the number of sources and to improve the quality of reconstructed images. With the proposed strategy integrated in the regularization-based reconstruction process, reconstruction algorithms need no a priori knowledge of source number; even more importantly, they can automatically reconstruct multiple sources that differ greatly in density or power.